PENGEMBANGAN MODEL TALKING STICKS DALAM KETERAMPILAN BERBICARA BAHASA INGGRIS PADA SISWA KELAS X (IPA 1) DI SMAN 4 BANGKALAN- MADURA - Wahyudi, Moh. Arief (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
There is a learning model that can help teachers in class X of Senior high schools in the field of study of the English language namely a Talking Sticks Model. The researchers used a Descriptive Qualitative method with the instrument of observation check list by three meeting times. Generated data that the total number of scores on the answer "yes" numbered 9 and "no" numbered 0. The number of indicators was 9 and concluded class X (IPA 1) SMAN 4 was success by using Talking Sticks to express his opinions / ideas in the English language. Then the model development in this study of learning English speaking skills a particular have been successfully applied in at classroom in the form of discussion and can improve students' speaking skill.